Penentuan Kandungan Unsur Krom dalam Limbah Tekstil dengan Metode Analisis Pengaktifan Neutron - Khaerani, Nina; Azam, Much.; Firdausi, K. Sofjan; Soeleman, Soeleman (BERKALA FISIKA, 2007)
A determination of chromium which consisted in textile cesspool one of the company of textile residing in Ungaran using neutron activation analysis method.The sample has been threated in the form of sediment sample and liquid sample. The sample then an irradiated by Lazy Susan irradiation facility at Kartini reactor for six hours and then the counting is done by HPGe detector for 300 seconds. The qualitative results shown that samples contents Cr-51. The quantitatively sediment sample chromium element rate equal to 491. 67 ppm and liquid sample chromium element rate equal to 0.011 ppm Key words: Neutron Activation Analysis, irradiation.